Composição florística, relação vegetação-solo e carbono em formações florestais naturais do Paraguai - Díaz, Lila Mabel Gamarra Ruíz (2020)
The general objective of the present study was to characterize the different forest formations present in Paraguay, in terms of their structure and floristic composition, to determine possible relations with edaphic variables and to estimate the carbon stock per ha. They were selected at random 100 sample units (AU) of 60 mx 60 m, distributed in five tree layers (20 AU for each layer: Dry Chaco Forest, Forest Sub-wet Flooded Paraguay River, Palm trees Forest, Subwetlands of the Cerrado and Moist Forest of the Eastern Region), located throughout Paraguay. It has records of diameters of 1.30 m high (d1.30) of all the bush-tree-d1.30 living individuals ≥ 5 cm. The floristic composition was analyzed for the number of species, genera and botanical families registered in each stratum, where, the floristic similarity was determined using the Jaccard similarity index, the richness using the Jackknife I estimator and species diversity through Diversity profiles from Rényi's exponential series. phytosociological The characterization of the horizontal structure of each stratum was made from the phytosociological parameters and the analysis of indicator species was used combining data of abundance and presence in the strata. The construction of the vegetation matrices and edaphic variables was carried out by means of a preliminary analysis, in which those that had no influence were removed. The correlation between vegetation data and edaphic variables was performed using the Canonical Correlation Analysis, to determine whether soil variables influence the presence of species and by Canonical Redundancy Analysis to assess whether which soil variables had the greatest influence on individuals. For the biomass calculations, specific allometric equations for four strata were used and for carbon the IPCC standard mean factor suggested for subtropical forests was used. In the different strata sampled there was a total floristic dissimilarity, mainly due to the great distances that exist between the strata. The most representative families (wealth) were Fabaceae, Myrtaceae, Rutaceae, Bignoniaceae and Euphorbiaceae. It was found that the different soil variables influence the presence and behavior of the sampled species and the strong correlation between organic material and organic carbon, in addition to silt and clay, stands out. The Moist Forest of the Eastern Region showed higher values of aerial carbon, due to the characteristics of this type of forest formation related to its structure, composition, soil fertility, water availability, among others, especially species such as Handroanthus sp., Caesalpinia paraguariensis, Schinopsis lorentzii and Jacaratia spinosa in the different strata sampled.